Of people, politics and profit: The political economy of Chinese industrial zone development in Nigeria - Clarke, N; Nikia Clarke (2014)
This project approaches ongoing debates over the impact of increased Chinese engagement in African countries through the lens of production and industrialisation. Emerging market FDI into Africa is growing rapidly, and an increasing proportion of this investment is into manufacturing and productive sectors. This trend is led by the commercial expansion of private Chinese manufacturing firms across the continent. The goal of this project is to examine the differentiated impacts on African industrialisation attempts of this phenomenon. It takes as its case study industrial zone development projects in Nigeria, namely, the two official economic and trade cooperation zones being developed as large-scale FDI projects by Chinese firms, with Chinese and Nigerian government support, in Lagos and Ogun states. Analytically, four dimensions of this process are identified for study: the home country context, the host country context, the zone structures and institutions, and the firms themselves. Special attention is paid to the interface between foreign actors and the particular political economy of Nigerian manufacturing, as well as the at times substantial gaps between policy and practice in terms of industrial planning, investment and production. The thesis argues that SEZ projects in general, including the Chinese ETCZs, are industrial policy tools that operate on particular assumptions regarding the organisation of global production. As such, they incentivise the insertion of export-oriented firms into established global networks supplying international markets. However, a closer examination of industrial policy in China, the production environment in Nigeria and the behaviour of internationalising firms reveals that these assumptions are not always accurate. Thus, the SEZ institution as it is currently conceived in Nigeria is ill-suited to lend support to the trend towards Chinese relocation of producer firms, as well as to the reality of Nigerian production—both of which are predicated on domestic and regional markets as the primary driver of African industrialisation and productive sector growth.